Biomechanical comparison of dynamic condylar screw and locking compression plate fixation in unstable distal femoral fractures: An in vitro study - Singh A.K.; Rastogi A.; Singh V. (My University, 2025)
Background: Distal femur fractures are difficult to manage and the selection of implant for internal fixation remains controversial. The objective of this study is to establish the relative strength of fixation of a distal femoral locking plate (DFLP) compared with the dynamic condylar screw (DCS) in the distal femur fractures. Materials and Methods: Study was conducted on 16 freshly harvested cadaveric distal femoral specimens, eight implanted with DCS and other eight with DFLP. The construct was made unstable by removing a standard sized medial wedge of 1 cm base (gap-osteotomy) beginning 6 cm proximal to the lateral joint line in distal metaphyseal region with the loss of medial buttress. Fatigue test was conducted under load control mode at the frequency of I Hz. Specimens were subjected to cyclic loading of 2 kN, under observation for 50,000 cycles or until failure/cutout, which ever occurred earlier. Results: In DFLP group, there was no implant failure and the average number of cycles sustained was 50,000. Six out of eight specimens completed 50,000 cycles and two failed in DCS group. The average number of cycles sustained by DCS was 46150. Though the bone quality as assessed by dual energy X-ray absorptiometry DEXA was comparable in both DFLP and DCS group ( P = 0.06), none failed in DFLP group and subsidence was 1.02 ± 0.34 mm (range: 0.60-1.32 mm), which was significantly 43% lower ( P = 0.006) than subsidence in DCS group (1.82 ± 0.58; range: 1.20-3.08 mm). The average stiffness of DCS group was 52.8 ± 4.2 N/mm, which was significantly lower than average stiffness of locked condylar plate group (71.2 ± 5.1 N/mm) ( P = 0.02). Conclusions: DFLP fixation of the distal femur fractures resulted in stronger construct than the DCS fixation in both cyclic loading and ultimate strength in biomechanical testing of a simulated A3 distal femur fracture.